Papel da lipocalina associada à gelatinase neutrofílica (NGAL) urinária na nefrotoxicidade da cisplatina em pacientes com câncer de cabeça e de pescoço - Cunha Júnior, Ademar Dantas da (2014)
Acute kidney injury (AKI) in patients receiving cisplatin is common, therefore the evaluation of renal function in patients on use of nephrotoxic drugs is fundamental. Objective: To evaluate the incidence of AKI and the role of lipocalin associated to neutrophil gelatinase (NGAL) in the monitoring of renal function in patients with head and neck cancer (HNC) who received cisplatin. Methods: We prospectively studied 50 patients with HNC treated with three sessions of cisplatin. Blood and urine were collected 24 h before cisplatin, 24 h after infusion, 48 h after each application and 35 days after the end of treatment (urine NGAL, C-reactive protein, creatinine, glomerular filtration rate, plasma lactate dehydrogenase and magnesium). Results: AKI was observed in 78 % of patients. There was increase in creatinina, and decrease in GFR after each cycle of cisplatin, and increased urine NGAL. Positive association was observed between the levels of NGAL, creatinine and C-reactive protein. It was observed an increase in creatinine, NGAL, C-reactive protein and decreased GFR in AKI patients compared to patients without AKI. Conclusion: AKI was noted in 78 % of patients with HNC treated with cisplatin and showed the correlation of NGAL with creatinine and GFR in demonstrating renal injury. NGAL levels may be elevated compared to baseline levels, even before the use of cisplatin